The Food Recall Manual - Douglas L. Archer; Keith R. Schneider; W. Steve Otwell; Renee M. Goodrich; Chris Thomas (EDIS)
The Food Science and Human Nutrition Department of the University of Florida has assembled this manual to assist food businesses, at all parts of the food chain, in learning to conduct rapid and effective product recalls. This document is FSHN 04-10, published: December 2004.